Analysis of Non-Tax Revenues from Driving License: Magnitude, Gaps, Determinants, and Implications for Police Transformation - Shinta Novita Sari; Harry Mustari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines non-tax state revenue from driving license retribution in the Indonesian National Police, emphasizing transparency, accountability, and key influencing factors during 2009–2012, with an evaluation extended to 2023–2024. The research aims to measure gaps between potential and actual revenue, assess transparency mechanisms, analyze the effects of motor vehicle numbers, population aged 15 and above, and related expenditure, and evaluate implications for police transformation. A quantitative descriptive method calculated potential revenue from issued licenses and tariffs, compared to actual realizations. Panel data regression with generalized least squares tested the factors across 31 provinces. Results reveal an average gap of negative 14.86 percent in 2009–2012 due to reporting errors and blank distribution issues. All factors positively affect revenue, with expenditure showing the strongest impact at 0.42 percent per one percent increase. The gap improved to negative 4.71 percent in 2023–2024, indicating partial progress. Enhancing administrative accuracy, optimizing expenditure, and improving transparency are essential to maximize revenue and advance police governance and accountability.